Intramyocardial immunomodulation with human CD16+ monocytes to treat myocardial infarction in pig: a blind randomized preclinical trial - Ascione, Raimondo; Bruno, Vito D.; Johnson, Tom; Sammut, Eva; Bond, Andrew; Lopez-Baz, Daniel; Deutsch, Julia; Bailey, Mick; Chiribiri, Amedeo; Patel, Ashish; Baker, Andrew; Modarai, Bijan (Frontiers in Cardiovascular Medicine, 2024)
Background Human CD16+ monocytes (hCD16+ Ms) have proangiogenic properties. We assessed the feasibility, safety and efficacy of hCD16+ Ms in a porcine model of myocardial infarction (MI). Methods and results A total of 27 female Large White pigs underwent MI with reperfusion and cardiac magnetic resonance (CMR). Five days later, animals received intramyocardial injections of hCD16+ Ms in saline (n = 13) or saline only (n = 14). hCD16+ Ms were selected from leucocyte cones. Feasibility/safety endpoints included injury at injected sites, malignant arrhythmias, cancer, haematoma, left ventricular (LV) dilatation, troponin release and downstream organ injury. Co-primary efficacy outcome included LV scar and ejection fraction (LVEF) at 30-day post-injections by CMR. Immunohistochemistry included neo-angiogenesis, fibrosis, markers of myofibroblast and inflammation. Four animals were excluded before injections due to untreatable malignant arrhythmias or lung injury. Median cell number and viability were 48.75 million and 87%, respectively. No feasibility/safety concerns were associated with the use of hCD16+ Ms. The LV scar dropped by 14.5gr (from 25.45 ± 8.24 to 10.8 ± 3.4 gr; −55%) and 6.4gr (from 18.83 ± 5.06 to 12.4 ± 3.9gr; −30%) in the hCD16+ Ms and control groups, respectively (p = 0.015). The 30-day LVEF did not differ between groups, but a prespecified sub-analysis within the hCD16+ Ms group showed that LVEF was 2.8% higher and LV scar 1.9gr lower in the subgroup receiving a higher cell dose. Higher tissue levels of neo-angiogenesis, myofibroblast and IL-6 and lower levels of TGF-β were observed in the hCD16+ Ms group. Conclusions The use of hCD16+ Ms in acute MI is feasible, safe and associated with reduced LV scar size, increased tissue levels of neo-angiogenesis, myofibroblasts and IL-6 and reduced pro-fibrotic TGF-β at 30-day post-injections. A higher cell dose might increase the LVEF effect while reducing scar size, but this warrants validation in future studies.